Synthesis and spectral characteristics of dyads based on tetraphenylporphyrin derivatives - N. V. Konovalova; E. V. Kirienko; V. N. Luzgina (Тонкие химические технологии, 2006)
The dyads composed of 2-(2-carboxyvinyl)-5,10,20-tetraphenylporphyrin and zinc complex of 5-(p-aminophenyl)-10,15,20-triphenylporphyrin were synthesized and their spectral and photophysical properties were studied